2016
DOI: 10.1016/j.antiviral.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring resistance mutations within the core and NS5B regions in hepatitis C genotypes, particularly genotype 5a, in South Africa

Abstract: Approximately 1 million South Africans are infected with Hepatitis C virus (HCV). The standard of care (SOC) in South Africa is combination therapy (pegylated interferon and ribavirin). HCV genotypes and/or mutations in the core/ non-structural regions have been associated with response to therapy and/or disease progression. This study examines mutations in the core (29-280 amino acids, including ~90 E1 amino acids) and NS5B (241-306 amino acids) regions on pre-treatment isolates from patients attending Johann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…From the analysis with the GenBank genotype 5 sequences, it was interesting to note that 81% of the references contained the R70Q mutation compared to 16% with the wildtype amino acid. In a study conducted in South Africa, the R70Q mutation was observed in 90% of genotype 5a blood donors [33]. Whether the impact of this mutation in genotype 1 strains is the same in genotype 5 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis with the GenBank genotype 5 sequences, it was interesting to note that 81% of the references contained the R70Q mutation compared to 16% with the wildtype amino acid. In a study conducted in South Africa, the R70Q mutation was observed in 90% of genotype 5a blood donors [33]. Whether the impact of this mutation in genotype 1 strains is the same in genotype 5 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the impact of this mutation in genotype 1 strains is the same in genotype 5 remains unclear. Presence of this mutation in only genotype 5 isolates could either be due to transmission of a mutated strain or a naturally occurring drug resistant mutation to the SOC [33]. However, the latter assumption cannot be confirmed since there are no data on duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HCV Genotype 4, however, resembles genotype 1 in both clinical and economic aspects. As for genotype 5, only one study from South Africa, where genotype 5 is the predominant infection, found that treatment with SOF‐LDV was cost‐effective at the listed price and would be cost‐saving at lower prices available in Egypt and elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that amino acid mutations in other regions of NS5B are associated with resistance to NS5B polymerase inhibitors. These amino acid residues include S96, S365, S368, M414, L419, M423, Y448, I482, V494, P495, V499, G554, and D559 [Aissa et al, ; Prabdial‐Sing et al, ; Sarrazin, ]. To achieve the high efficacy for drug treatment, it may be important to investigate amino acid mutations of the entire NS5B region.…”
Section: Discussionmentioning
confidence: 99%